The Effects of Arbuscular Mycorrhizal Fungal Inoculation and Mulch of Contrasting Chemical Composition on the Yield of Cassava under Humid Tropical Conditions - Iniobong E. Okon; M. G. Solomon; O. Osonubi (The Scientific World Journal)
The influence of arbuscular mycorrhizal fungus (AMF), Glomus deserticola, and leaf mulch from Gliricidia sepium and Senna siamea on the yield of cassava (Manihot esculenta) in a degraded alfisol of southwestern Nigeria was investigated. Inoculation in conjunction with mulching increased cassava tuber yield by 40–278% over the control. The highest yield was obtained with G. sepium and S. siamea mulch applied together in equal proportions. The results are explained in the light of the growth-enhancing effects of AMF, encouraged by the ameliorating effects of mulch on the soil structure and nutrient contents.